1998
DOI: 10.1021/jp981040g
|View full text |Cite
|
Sign up to set email alerts
|

Nonconformal Potentials and Second Virial Coefficients in Molecular Fluids. II. Applications to Nonspherical Molecules

Abstract: A theory recently proposed characterizes effective two-body interactions in gases by molecular sizes and energies plus effective measures of the nonconformality between the exact potential and a spherical reference. This theory provides a procedure to construct effective potentials which reproduce the second virial coefficients B(T) of the substance of interest and allows us to express B(T) in simple and compact form. In this paper we test the applicability of the theory to a variety of nonspherical modelsssph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…We have shown that the potentials u ( r , Ω) and u 0 ( r ) may be related by introducing a relative measure of the difference between their profiles in a u vs r 3 plot. When the nonconformality between both potentials is such that it can be described by a constant parameter S , we have further shown that the virial coefficients B ( T ) and B 0 ( T ) are explicitly and very simply related. , Although there are pairs of potentials u ( r ,Ω) and u 0 ( r ) for which S is strictly constant and for them this NC theory is exact, the study of a great variety of widely used model systems, both spherical and nonspherical, has shown that assuming S to be constant leads to approximate results of high accuracy . We refer to this as the approximate nonconformal (ANC) theory, which in general allows us to use two values, S R and S A , of the softness parameter to describe the repulsive and attractive parts of the u vs r 3 profile, respectively.…”
Section: Theorymentioning
confidence: 78%
See 2 more Smart Citations
“…We have shown that the potentials u ( r , Ω) and u 0 ( r ) may be related by introducing a relative measure of the difference between their profiles in a u vs r 3 plot. When the nonconformality between both potentials is such that it can be described by a constant parameter S , we have further shown that the virial coefficients B ( T ) and B 0 ( T ) are explicitly and very simply related. , Although there are pairs of potentials u ( r ,Ω) and u 0 ( r ) for which S is strictly constant and for them this NC theory is exact, the study of a great variety of widely used model systems, both spherical and nonspherical, has shown that assuming S to be constant leads to approximate results of high accuracy . We refer to this as the approximate nonconformal (ANC) theory, which in general allows us to use two values, S R and S A , of the softness parameter to describe the repulsive and attractive parts of the u vs r 3 profile, respectively.…”
Section: Theorymentioning
confidence: 78%
“…18,20 Although there are pairs of potentials u(r,Ω) and u 0 (r) for which S is strictly constant and for them this NC theory is exact, the study of a great variety of widely used model systems, both spherical and nonspherical, has shown that assuming S to be constant leads to approximate results of high accuracy. 19 We refer to this as the approximate nonconformal (ANC) theory, which in general allows us to use two values, S R and S A , of the softness parameter to describe the repulsive and attractive parts of the u vs r 3 profile, respectively.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Within the simpler non-polar models are those that represent the CO molecule as a spherical Lennard-Jones site without charges (1CLJ), developed mainly from viscosity data [6][7][8] or the second virial coefficient [9][10][11], although in recent years, these models have also been used to study the separation of CO and H 2 on carbon nanotubes [12]. Another model proposes a rigid molecule composed of two equal L-J centers (2CLJ) located at each atom [13], which has been used to study the thermal conductivity of liquid CO [14] and its solubility in ionic liquids [15].…”
Section: Introductionmentioning
confidence: 99%
“…La ec. (1.22) se cumple con muy buena aproximación para moléculas de gases nobles, diatómicas no polares o poco polares, alcanos, perfluoroalcanos y percloroalcanos, entre otras [17].…”
Section: No Conformalidad Y Teoría Ancunclassified